Minimally Invasive Versus Open Akin Osteotomy: A Comparative Study - Sebastian Schilde MD; Natalia Gutteck MD; Karl-Stefan Delank PhD (Foot & Ankle Orthopaedics, 2020)
Category: Midfoot/Forefoot; Bunion Introduction/Purpose: Minimally invasive techniques of Akin osteotomy grow in popularity in order to minimize wound healing problems. To date it is recommended to keep the lateral corticalis intact during first phalanx osteotomy. The lack of direct visual control makes this a challenging goal in minimally invasive surgery. This retrospective study investigates whether or not the perforation of the lateral corticalis causes clinical or radiological negative effects. The quality of fixation with crossed K-wires and double threaded screws is compared. Methods: 184 patients (210 feet) with symptomatic mild to severe hallux valgus deformity and pathological interphalangeal angle (IPA) of at least 10° underwent surgery combined with Akin osteotomy. 124 minimally invasive Akin osteotomies were fixed with two crossing K-wires and compared to 86 Akin osteotomies in open technique with double threaded screw fixation. After 6 and 12 weeks IPA and bony consolidation were assessed. Results: Preoperative interphalangeal angles were mean 13.4° (+- 3.6°) (minimally invasive group (MI)), or 13.3° (+- 3.5°) (open surgery group (OS)) degrees (p>0.05).Perforation of the lateral corticalis occurred in 12 (13.9%) (OS), or 64 (51.6%) cases (MI), respectively.12 weeks after surgery the mean IPA was 4.1° (+- 1.4°) (MI), or 4.8° (+- 1.2°) in the open surgery group (OS) (p > 0.05).Bony consolidation was noticed after 6 weeks (OS, double threaded screw) or 12 weeks (MI, crossing K-wires).Three deep infections occurred in the OS group after Lapidus arthrodesis and two deep infections were registered in the MI group after MICA. All patients required revision with removal of implants. Pseudarthrosis did not occur in any group. Conclusion: Perforation of the lateral corticalis did not cause negative effects on bone healing or IPA. Minimally invasive Akin osteotomy provides equivalent correction of IPA compared to open surgery with a slightly prolonged radiological bony consolidation. The fixation technique had no influence on IPA correction.